Prohibitionist Protests by Women in India's Northeast. Issue 2 (December 2016) - Deka, Kaustubh
The body of women in India's northeast is both racialized and gendered as the region continues to be constructed through the binaries of post-colonial sate-society conflicts and often treated as the 'other' of the nation state. A conflict centric approach however has mostly focused on women's interventions in the society from the perspective of their 'peace making' capacities and thus obscuring some other significant roles performed historically by organized women power in the region: activities that predate and, in fact, in some crucial ways influence their gradual mobilization towards the role of peace making. Some of the prominent women led social movements that began in the decades of 1970s and 1980s around the issue of alcohol prohibition had gradually transformed into movements taking up issues of human rights violations and peace negotiations besides others. In this context it is interesting to look into the instances of anti-alcohol or prohibitionist protests undertaken by women in India's northeast, specially focusing on prominent women's groups in the states of Manipur and Nagaland, that points at the complex roles played by women's groups in crafting a public space for the women to articulate their opinion in these societies even when they face challenges from within and without and come to terms with the dilemmas of having to take some difficult position both against the state and the community.